1975
DOI: 10.1073/pnas.72.4.1550
|View full text |Cite
|
Sign up to set email alerts
|

Relative numbers of human globin genes assayed with purified alpha and beta complementary human DNA.

Abstract: IPurified a and 63 globin complementary DNAs (cDNAs) have been separated from total radioactively labeled human globin cDNA using mRNA purified' from liver of a hydrops fetalis (a thalassemia). The P cDNA hybridizes to the hydrops fetalis mRNA while the a eDNA remains single-stranded. The purified a and iB cDNAs were assayed for their purity by their hybridization to mRNA prepared from reticulocytes of nonthalas.semia, a thalassemia, and I thalassemia subjects. The results indicate that the separated cDNAs are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

1976
1976
2001
2001

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 15 publications
1
25
0
Order By: Relevance
“…The results also provide insights into the molecular defect in thalassemia at the gene level. We and others have previously shown that in p8-and 80-thalassemia, structural f-globin genes are present in normal amounts (5,10). It is postulated by us and others (32,33) that regulatory DNA sequences in the linked y-8-,3-gene sequences are responsible for the expression of these genes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results also provide insights into the molecular defect in thalassemia at the gene level. We and others have previously shown that in p8-and 80-thalassemia, structural f-globin genes are present in normal amounts (5,10). It is postulated by us and others (32,33) that regulatory DNA sequences in the linked y-8-,3-gene sequences are responsible for the expression of these genes.…”
Section: Resultsmentioning
confidence: 99%
“…A role is postulated for the DNA sequences between the y-, 8-, and ,8-genes in limiting y-globin gene expression in the B3-thalassemias. We and others (6,7,11,12) have previously shown that extensive deletion of 8-globin genes, and probably 8-genes as well, in 8,8-thalassemia and hereditary persistence of fetal Hb is associated with greater y-globin gene expression, in contrast to ,0-and 8+-thalassemia in which no deletion of 8-and /8-structural genes is detectable (5,10). Similarly, in the Lepore homozygote the presence of a fusion-gene product including the N-terminal end of 8-globin suggests that DNA sequences between y-and 8-genes are intact and may account for the (36) and rabbit 8-globin genes (37); in the mouse it has been shown that these intervening sequences are transcribed into nuclear globin RNA precursors (38), although they are not present in mature mouse globin mRNA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most often, there are decreased amounts of the specific globin messenger RNA which serves as a template for the synthesis of the affected globin chain (4)(5)(6). The messenger RNA deficit results from either globin gene deletions (7)(8)(9)(10) or transcriptional or post-transcriptional impairment of the expression of globin genes (11)(12)(13). Analysis of the hemoglobins synthesized in patients with thalassemia has not shown abnormalities in the primary structure of the globin chains (1)(2)(3).…”
Section: Introductionmentioning
confidence: 99%
“…Implications for the a-thalassemia syndromes Recent studies (4,(23)(24)(25) indicate that a-thalassemia may be caused by at least partial deletion of the a-chain structural genes. The varying degrees of severity in the a-thalassemia syndromes are believed to reflect the number of a-chain genes deleted.…”
Section: Methodsmentioning
confidence: 99%